Early Organization of the Self from a Neuroaffective Complexity Standpoint - Guajardo-Sainz, H; Kushner-Lanis, D; Lecannelier-Acevedo, F (REVISTA PSIQUIATRIA & PSICOLOGIA HUMANISTA, S L, 2019)
Cognitive postrationalist model has been ahead of his time in a series of epistemological and psychological approaches. Evolutionary constructivist notion has, until today, paradigmatic repercussions for the praxis of sciences of mental life, that even postracionalism itself couldn t assume in a complete and revolutionary manner. Embodied circular dynamic between observer and observedforces to changes (and annulments) in the explanation, classification, and intervention in what has been called "psychopathology". Under a strong postrationalist influence, but integrating currents approach in complex systems models, theory of attachment, neuro-affectivity and models of human development, this paper present the main principles of an approach that seek to complete and fully assume evolutionary complexityproposals of Vittorio Guidano. This proposal seeks to expand the theory of the legacy of early attachments in the functioning of the self as well his repercussions on psychopathology and psychotherapeutic interventions.